2008
DOI: 10.1002/sia.2910
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cu segregation to oxide–metal interface of Ni‐based alloy in a metal‐dusting environment

Abstract: Hard X-ray photoelectron spectroscopy (HX-PES) has been realized using high-brilliance synchrotron radiation. High-energy photon excitation enables us to probe photoelectrons with larger escape depth compared to conventional PES. This allows us to conduct, without destruction, a study of the embedded interface of materials as the oxide-metal interface. We apply HX-PES to investigate for Cu segregation in the oxide-metal interface during metal-dusting corrosion. The effective concentration of Cu in the segregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…photoelectron spectroscopy by means of synchrotron source[30]. The thickness of Cusegregation layer formed below the Cr 2 O 3 scale was about 0.25nm and Cu content was about 50%.Although the alloy and oxidation condition in the present study is different, Cu segregation at the scale/alloy interface in the initial oxidation stage in the present study is expected, because Cu cannot be oxidized once a NiO scale is formed as shown in Fig.…”
mentioning
confidence: 53%
“…photoelectron spectroscopy by means of synchrotron source[30]. The thickness of Cusegregation layer formed below the Cr 2 O 3 scale was about 0.25nm and Cu content was about 50%.Although the alloy and oxidation condition in the present study is different, Cu segregation at the scale/alloy interface in the initial oxidation stage in the present study is expected, because Cu cannot be oxidized once a NiO scale is formed as shown in Fig.…”
mentioning
confidence: 53%
“…One of evidences has been demonstrated by using hard X-ray photoelectron spectroscopy (HX-PES). 29 At high temperatures, Cu was segregated at a few atomic layers between oxide /metal interface of Ni-Cr-Cu alloys. For the Ni-17.2 at.% Cu alloy, Cu has greatly segregated at 65at.% on the alloy surface after heating at 923 K for 10min.…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that the corrosion resistance against the metal dusting was improved because of Cu segregation on the Ni‐based alloy in the metal dusting environments. In a previous work, we showed that Cu segregates in the oxide–metal interface of Ni–Cr–Cu alloys exposed to the metal dusting environment by hard X‐ray photoelectron spectroscopy . However, the segregation behavior of Cu under the oxidation environment has not become clear.…”
Section: Introductionmentioning
confidence: 99%